2016
DOI: 10.1038/srep38034
|View full text |Cite
|
Sign up to set email alerts
|

Greater efficacy of atorvastatin versus a non-statin lipid-lowering agent against renal injury: potential role as a histone deacetylase inhibitor

Abstract: Statins, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitors have been shown to improve diabetic nephropathy. However, whether they provide protection via Histone deacetylases (HDAC) inhibition is not clear. We conducted a comparative evaluation of Atorvastatin (AT) versus the non-statin cholesterol-lowering drug, Ezetimibe (EZT) on severity of diabetic nephropathy. Streptozotocin-treated male Wistar rats were fed a cholesterol-supplemented diet and gavaged daily with vehicle, AT or EZT. Control rats r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…In this study, the use of statins and ezetimibe was reported by our participants. Ezetimibe's effect of decreasing blood glucose has been revealed by studies, while statins have been proved to increase the risk of developing type 2 diabetes . We analysed the effects of these medications on the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the use of statins and ezetimibe was reported by our participants. Ezetimibe's effect of decreasing blood glucose has been revealed by studies, while statins have been proved to increase the risk of developing type 2 diabetes . We analysed the effects of these medications on the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs also have had favourable effects on renal function in clinical trials, particularly in patients with diabetes; long‐term therapy reduces albuminuria and retards the decline in glomerular filtration rate . Similar benefits to the kidney have been noted in experimental diabetes; in these studies, statins prevent oxidative stress and cellular injury as well as the inflammatory, proliferative and fibrotic changes that are characteristic of diabetic chronic renal disease . These favourable effects cannot be fully explained by the actions of these drugs on lipids; other lipid‐lowering drugs exert little or modest effects on albuminuria and may worsen renal function in patients with diabetes .…”
Section: Effect Of Drugs Used In Diabetes On the Sodium‐hydrogen Exchmentioning
confidence: 60%
“…9,211,212 Similar benefits to the kidney have been noted in experimental diabetes; in these studies, statins prevent oxidative stress and cellular injury as well as the inflammatory, proliferative and fibrotic changes that are characteristic of diabetic chronic renal disease. [213][214][215][216][217][218][219][220] These favourable effects cannot be fully explained by the actions of these drugs on lipids; other lipid-lowering drugs exert little or modest effects on albuminuria and may worsen renal function in patients with diabetes. [221][222][223][224] It is therefore noteworthy that statins inhibit NHE activity in experimental and clinical studies.…”
Section: Inhibitors Of Aldosterone Action and Cholesterol Synthesismentioning
confidence: 99%
“…This switch is accomplished by the modulation of acetylation of lysine 16 in histone H4 (H4K16ac), a DMAP1-induced, acting in inter-nucleosome interaction and as a scaffold for other transcription factors and chromatin-modifying proteins [92,93]. A growing body of evidences suggests that statins can promote the acetylation of H3 and H4 histones [45,78,94]. Thus, the increase of dmap1 transcription may be directly related with the increasing transcription of several genes or through the negative feedback required for the protection of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanism(s) of the observed SIM effects are poorly understood, previous studies with mammalian cell lines suggested that this pharmaceutical is able to modulate the regulation of the epigenome (e.g. DNA Methylation, histone acetylation and ncRNAs) [42][43][44][45][46]. Alterations in DNA methylation have previously been associated with downregulation or inhibition of DNA methyltransferase 1 (DNMT1), a critical protein responsible for maintenance of DNA methylation patterns [47,48].…”
Section: Introductionmentioning
confidence: 99%